Bioturbation as a mechanism for radionuclide transport in soil: Relevance of earthworms - Müller-Lemans, Hans; van Dorp, Frits (Journal of environmental radioactivity, 1996)
In the context of safety analyses performed for radioactive waste repositories, one important group of scenarios assumes that radionuclides escaping from a repository will reach the biosphere via groundwater. Consequently, when calculating radionuclide migration in the biosphere, most of the models used to date concentrate on transport in the liquid phase. In the soil, however, transport in the solid phase can also be important, particularly when burrowing animals displace the soil together with sorbed and low-solubility radionuclides. Given the conditions prevailing in agricultural areas of central Europe, it is mainly earthworms which play a significant role in material displacement and these will be the subject of this report. According to the current data, it will take around 5–20 years for the earthworms to turn over the top soil of grasslands once, a process which results in intensive and more or less homogeneous mixing of the soil. Earthworms transport around 2 kg m −2 year −1 of dry matter from deep soil to top soil. A numerical example is used to present the equations which, for given distribution coefficients, can be applied to calculate the portions of the transfer coefficient which can be attributed to transport in the liquid and solid phases. The results demonstrate that material transport by soil fauna, and particularly by earthworms, is a relevant mechanism in many cases, especially for the upward transport of strongly sorbing radionuclides. It should therefore be considered in biosphere models.